An Introduction to HTML and JavaScript for Scientists and Engineers - Brooks, David R. (Springer London : Imprint: Springer, 2007)
The JavaScript language is widely used for simple online applications. This useful book presents HTML and JavaScript in a way that uniquely meets the needs of students in the sciences and engineering. It explains how to create simple, client-side applications for scientific and engineering calculations. It includes many complete HTML/JavaScript examples with science/engineering applications to guide the reader progressively and comprehensively through the subject. This book is specifically targeted at a technical audience-- but not one that is necessarily familiar with a programming language-- and gives the reader a sufficient understanding of HTML and JavaScript to write their own online applications. The exposition emphasises basic programming principles in a modern Web-oriented environment, making it also highly suitable for an introductory programming course for non-computer-science majors. Features and topics: • Includes detailed code examples and output to guide the reader • Is extremely accessible, and ideal for self-study • Offers a working knowledge of HTML and JavaScript, which are essential for Web development and useful as a marketable skill • Written specifically to meet the needs of science and engineering students and working professionals • Provides an author-supported supplementary website containing code examples and all graphics files: www.pages.drexel.edu/~brooksdr/DRB_web_page/BookCode/BookCode.htm. Introduction to HTML and JavaScript for Scientists and Engineers addresses directly the needs of engineers and scientists by explaining just those components of HTML and JavaScript needed to write their own online applications. The book will prove an indispensable introduction and guide for professionals, as well for students interested in learning about these useful tools. Dr Brooks has authored the successful Springer titles, Problem solving with Fortran 90 for Scientists and Engineers, and C Programming: The Essentials for Engineers and Scientists.